Melanocytic nevi. I. Epidermal melanocytic nevi, dermal melanocytic nevi. - Bonifazi, E.; Ferrante, M.R.; Bellomo, G.; Caprio, F. (European Journal of Pediatric Dermatology, 2001)
In the previous issue, which was devoted to prepubertal melanoma, the congenital melanocytic nevus was treated due to its close relationship with this tumor. In this issue we face the complex chapter of melanocytic nevi. The cells which produce these nevi are the melanocytes and the nevus cells. According to some Authors this distinction is not necessarily well-founded since the nevus cells probably derive from melanocytes. We maintain that this distinction is useful not only for didactic purposes and classification, but also because the two cell types, independently of their origin, are significantly different morphologically and functionally. Apart from melanocytes and nevus cells, we shall discuss melanophages. (...)